Media in times of crisis : national and international issues - Chowdhury, Afsan (Dhaka : Shraban Prokashoni, 2003)
With reference to press and censorship of Bangladesh.
Includes bibliographical references.
Keywords: Mass media -- Bangladesh; Press -- Bangladesh; Communication -- Social aspects -- Bangladesh; Communication -- Social aspects; Mass media; Press; Bangladesh